Natural Bio-Enhancers: Scope for Newer Combinations- A Short Review - Nabarun Mukhopadhyay; Saleemulla Khan; Aswatha Ram H N (Journal of Global Pharma Technology, 2018)
Bio-enhancers are those chemical entities which promote absorption and augment the bioavailability of accompanyingdrugs and do not exhibit synergy. Natural bio-enhancers are the agents which are obtained naturally and can be used to promote and augment bioavailability of the poorly absorbed drugs, which are administered for long periods, expensive and exert toxic reactions. This approach of using natural bio-enhancer improves the bioavailability, efficacy, thereby reduces the dose and therefore, cost, toxicity and adverse effects. A number of medicinal plants have shown this property of enhancing bioavailability of other drugs. This review work was carried out by thorough searching of different research articles from different online journals from Pubmed, Google scholar, Science direct. We also searched the theories related to the topic from different books obtained from Manipal Health Sciences Library. In this review we have collected literature of scientifically validated plants having bio-enhancing property. It also describes the scopes of using newer combinations of natural and synthetic productsalongside natural bio-enhancers such as piperine, ginger, and aloes to name a few.For instance, the combination of curcumin with piperine enhances the bioavailability of the former, similarly, bioavailability of paclitaxel, a cytotoxic drug canbe improved by using quercetin combination. Thebio-enhancing effect of trikatu (a traditional Ayurvedic preparation) on cefquinome and tolfenamic acid has also been documented.